Pelatihan Dan Pendampingan Penyusunan Laporan Keuangan Bagi Wirausaha Muda (WIDA) Feb UNUD - Ni Nyoman Kerti Yasa; I G. A. K. Giantari; Henny Rahyuda; I G. A Dewi Adnyani; Ni Wayan Ekawati; I Gst. Ngr. Jaya Agung Widagda; Putu Laksmita Dewi Rahmayanti (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2023)
This community service was carried out against a background of conditions where Young Entrepreneurs (WIDA) of the Faculty of Economics and Business, Udayana University were not skilled in compiling Financial Report documents. This Financial Report document should be owned by every businessman in order to guide business managers in running their business so as to achieve high performance. This Financial Report document includes calculations about cash flow, preparation of General Ledgers, Balance Sheets, Profit/Loss Reports. Based on this phenomenon, it is felt necessary to prepare WIDA FEB Unud so that they have the ability to prepare Financial Report documents in a professional manner. The purpose of this community service is to build WIDA FEB's ability to prepare its Financial Statements. This service is in the form of one day training with resource persons: Dr. I Gusti Ngurah Agung Suaryana, SE, Msi, Ak, and continued with weekly consultations or assistance after 4 times. This service took place at FEB Unud, Floor 2 of the MM Building, by inviting 20 members of WIDA FEB Unud so that they were able to prepare and have Financial Report Documents for each business. After the dedication was carried out, WIDA FEB Unud was able to compile financial reports as a guideline for managing its assets and liabilities in order to be able to achieve higher financial performance.